Antibiotic inhibition of ribosome function - Wilson, Daniel (Henry Stewart Talks, 2008)
Overview of antibiotics that target the ribosome, Different mechanisms by which translation initiation inhibitors, such as kasugamycin and edeine, perturb initiator tRNA binding, Structural insight into how the thiopeptide class of antibiotics, such as thiostrepton and micrococcin, inhibit stable binding of translation factors, such as EF-G, to the ribosome, Mechanism by which drugs, such as chloramphenicol and macrolides inhibit the peptidyltransferase reaction, How species specific differences in antibiotic interaction sites between different organisms can have a dramatic influence on drug binding